PENGARUH PENERAPAN METODE PEMBELAJARAN TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMKN 26 JAKARTA - Mugiyono Mugiyono; Dhya Rahma Suci Mulya (Almarhalah, 2023)
ABSTRACTThis research is related to the decline in student learning outcomes because educators are not careful when choosing learning methods, especially in the practice of funeral prayers, this causes low student learning outcomes. The purpose of this study was to analyze and measure the impact of the implementation of the demonstration method on student learning outcomes and to analyze strategies for improving student learning outcomes in the practice of funeral prayers through demonstration methods. This study used a quantitative approach with a descriptive correlational analysis method using a questionnaire instrument distributed to 41 samples from a total of 467 population of class XII at SMKN 26 Jakarta. The questionnaire instrument consists of 20 positive and negative statements on variable X, as well as a list of test values for the practice of funeral prayers on variable Y. The results of this study are that there is an effect of the application of the demonstration learning method on student learning outcomes, seen from the correlation coefficient test yielding 0.525 and coefficient of determination of 0.276. The results (ro ) are greater than (rt) at a significant level of 5% of 0.316 and 1% of 0.408. Thus the null hypothesis is rejected, while the alternative hypothesis is accepted or approved, meaning that there is an effect of the application of the demonstration learning method on student learning outcomes of 0.525 or 52.5%.Keyword: Demonstration Methods, Learning Outcomes, Practices of Jenazah Prayers